1996
DOI: 10.1002/(sici)1520-6300(1996)8:2<159::aid-ajhb3>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Issues in the measurement of energy intake for free-living human populations

Abstract: Energy intake is the most difficult component of energy balance to measure. All known methods are subject to considerable error, both random error and bias. High variability within and between subjects means that sampling is important to increase reliability. Further, the fact that true intakes are unknown means that some outside measure of validity is desirable as a check on the accuracy of recording of habitual intake. This report examines food intake for populations where expenditure has been measured by do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…32 We used the 24 h record, which seems an accurate method to quantify diet of young children, 31,33 and allows classi®cation of the data, which is required for epidemiologic studies. 34 The accuracy of the 24 h record to analyze relations between food intake and anthropometry remains questionable: a single 24-h record cannot take into account the dayto-day variation of food intake and overestimates the extremes of the distribution. 35 Seasonal differences 33 were partly avoided in FLVS, which took place in spring.…”
Section: Discussionsupporting
confidence: 92%
“…32 We used the 24 h record, which seems an accurate method to quantify diet of young children, 31,33 and allows classi®cation of the data, which is required for epidemiologic studies. 34 The accuracy of the 24 h record to analyze relations between food intake and anthropometry remains questionable: a single 24-h record cannot take into account the dayto-day variation of food intake and overestimates the extremes of the distribution. 35 Seasonal differences 33 were partly avoided in FLVS, which took place in spring.…”
Section: Discussionsupporting
confidence: 92%
“…Individuals who may already be under-nourished might suffer negative energy balance if they carry heavy loads, a situation associated with a number of health problems including compromised physical and cognitive function (Kurpad et al, 2005), impaired immune function (Black et al, 2003) and, as we discuss below, impacts on reproduction. However, adequate assessment of energy balance is difficult to achieve because of both the well-documented difficulties of accurately 8 assessing energy intake (Huss-Ashmore, 1996), particularly in populations where food is typically eaten from a common bowl, and the energetic variability in 'real' load-carrying practices, which are intermittently combined with other highly energyintensive activities undertaken by African women. As a result, most studies (including those reported below) have been limited to energy expenditure only, under controlled treadmill conditions.…”
Section: A) Energy Costs Of Headloadingmentioning
confidence: 99%
“…Mathematical models and their numerical solutions can be used to quantify changes in body mass and are therefore useful tools for studying body mass. Caloric intake and total energy expenditure are two of the most important and complex factors that should be quantified [16] , [17] . Our aim in the present study is to propose a set of formulas as a function of individual body mass and implement them to estimate how body mass varies over time.…”
Section: Introductionmentioning
confidence: 99%